Outcome of arterial switch operation for transposition of the great arteries. A 35-year follow-up study. (1st October 2020) - Santens, Béatrice; Van De Bruaene, Alexander; De Meester, Pieter; Gewillig, Marc; Troost, Els; Claus, Piet; Bogaert, Jan; Budts, Werner
Abstract: Background: Arterial switch operation (ASO) is today the first-choice surgical treatment for patients with transposition of the great arteries. Long-term outcome data still remain scarce. Moreover, the course of these patients is not uneventful. Therefore, we wanted to evaluate long-term outcome and determine on which variables to focus during follow-up. Methods: Clinical records of 318 patients who underwent ASO between October 1981 and July 2018 were reviewed. Perioperative, post-operative, and interventional data were collected to determine mortality and the need for re-intervention. Descriptive statistics and Kaplan-Meier survival analysis were performed. Results: Mean follow-up time was 11.1 SD 8.5 years (range 0–35) with a mean age of 12.5 SD 9.0 years (range 0–37) at latest follow-up. In-hospital mortality was 7.5% and overall survival 90.9% for a maximum follow-up time of 35 years. Causes of early mortality were cardiogenic shock, severe pulmonary hypertension, septic shock and multiple organ failure. Causes of late mortality were cardiogenic shock, severe pulmonary hypertension, pacemaker lead fracture and fire death. Re-intervention free survival at 5-year was 91.6%, at 10-year 90.7%, at 20-year 79.2%. For all survivors, the most frequent sequelae after ASO were pulmonary artery stenosis (80.9%), of which 13.5% needed an intervention. The threshold for intervening on lesions at the level of the pulmonary artery bifurcation was higher and the percutaneous re-intervention rate was higher for non-bifurcation lesions. Conclusions: Despite a relatively high peri-operative mortality, TGA patients have an excellent overall long-term survival. However, a large proportion of patients requires re-interventions, mainly for pulmonary artery stenosis. Highlights: Long-term follow-up of arterial switch operation for TGA shows excellent survival. We compared overall survival with Belgian reference population. Reinterventions after ASO are not uncommon. Pulmonary artery stenosis was the most frequent late complication. Percutaneous re-intervention rate was higher for non-bifurcation lesions.